Durability and life prediction analysis of recycled aggregate concrete with ceramic waste powder under freeze-thaw conditions based on impact-echo method and Grey-Markov model - Yu, Jianqiao; Liu, Dawei; Zhang, Zhigang (Frontiers in Materials, 2022)
Utilizing recycled aggregate concrete (RAC) for cyclic usage in building materials is one of the most feasible methods for reducing the demand for natural aggregates in the construction sector and disposing of construction and demolition trash in landfills. Previous research has demonstrated that the weak freeze-thaw (F-T) resistance of RAC poses a significant threat to the safety of RAC structures in severe cold regions. Therefore, this paper explores the influence of ceramic waste powder (CWP) at various replacement rates on the freeze-thaw resilience of RAC. In this experiment, six groups of CWP doping ratios of 0%, 10%, 20%, 30%, 40, and 50% were designed. Before the F-T cycling test, each group of specimens’ basic mechanical and physical performance data was measured throughout the regular curing age. At the conclusion of each F-T cycle, the durability performance of RAC was tested using the impact-echo method and compressive strength test. To predict the lifetime of RAC mixtures, a Grey-Markov model was created. It was found that the impact-echo method is more appropriate for assessing the durability of RAC in a freeze-thaw condition. The RAC’s F-T resistance is greatest when the CWP content is 20%. The Grey-Markov model has a high degree of predictive accuracy, effectively reflecting the relationship between RAC durability and F-T cycles, and has wide practical applications.